The effect of cytotoxic treatment on bone tissue - Wojtacki, Janusz; Leśniewski-Kmak, Krzysztof; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Current knowledge about side effects of chemotherapy includes - besides many others - observations related to bone tissue. First publications concerning this problem date from sixties of 20th century. Initial data comes from oncology, haematology and internal medicine. The data was based on clinical examination, bone x-rays photos, knowledge arising from treatment and follow-up periods. It formed specific background and forced physicians to launch clinical trials, aimed to demonstrate and assess existing relationship between the phenomenon - namely osteopenia and osteoporosis - and cytotoxic treatment. It was bone mineral density (BMD) test to be found the main tool of estimation, but biochemistry investigations and quantitative assessment of bone radiostructure were useful as well. Patients - children and adults - suffering from collagen diseases, brain tumours, breast cancer, sarcomas, Hodgkin and non-Hodgkin lymphomas, and leukaemia (after standard or high dose chemotherapy with autologus blood stem cell transplantation) were subjects of all these trials. Several cytotoxic agents of different mechanisms of action (i.e. methotrexate, doxorubicin, busulfan, ifosfamide) reveal this kind of toxicity. Pain, fractures, certain changes in x-rays (Singh index), bone mineral density decrease etc. were described as main symptoms. Osteopenia and osteoporosis can be induced in different mechanisms: directly due to influence of cytotoxic treatment on bone tissue, and, what is also important, by ablative influence on gonads. The latest observation can be supported with several cases of osteopenia and osteoporosis in chemotherapy treated premenopausal women, developed due to premature amenorrhoea. Interestingly the same mechanism can also occur in men. On the other hand direct influence of cytotoxic treatment on bone tissue is also important. Another kind of investigations related to changes in bone tissue due to chemotherapy was conducted in laboratory, mainly using animal models. These studies gave an opportunity to demonstrate – by invasive methods - microscopic symptoms of chemotherapy effects on bone. Tissue histomorphometry revealed osteopenia in treated animals. Comparison of samples from treated and untreated groups demonstrated the remarkable decrement in bone mass, changes in matrix and bone cells activity. Chemotherapy is still one of the mainstays of anticancer management. It is important to remember about possibility of appearance not symptoms - not related to cancer but treatment - which can suggest metastatic disease. On the other hand osteopenia and osteoporosis may have important influence on quality of life, particularly in cases of young patients with good prognosis.